Principles, Foundations, and Implementation of Arabic Language Curriculum Development in Indonesia - Yazid Hady; Muhammad Zuhdi; Suparto Suparto; Maswani Maswani; Afsheen Fatima (Universitas Negeri Padang, 2026)
The development of the Arabic language curriculum in Indonesia holds a strategic position, both as a religious language and as an international language of communication. This article aims to examine the principles, foundations, and implementation of the Arabic language curriculum by referring to academic literature and the latest regulations, including the 2024 Learning Achievement (CP) documents and the Director General of Islamic Education Decree No. 3302 of 2024. The method used is literature review (library research) with a content analysis approach. The study results indicate that the development of the Arabic language curriculum is based on six dimensions: educational philosophy, Pancasila, linguistics, psychology, education, and the Arab-Islamic socio-cultural context. Curriculum implementation includes learning planning, innovative strategies, teaching material development, authentic assessment, the roles of teachers and institutions, the integration of local culture, and the utilisation of digital technology. In conclusion, the Arabic language curriculum in Indonesia must function as a religious, scientific, humanistic, and global instrument that produces graduates rooted in local culture but ready to face the challenges of international communication.